Bio-medical waste management in different hospitals of Guwahati and its effect on environment - Changmai, Arabinda; Islam, Tofiqul; Nongsiang, Dibarlan; Deka, Manoj Kumar; Saharia, Bhargab Jyoti; Choudhury, Ananta; Dey, Biplab K. (Journal of Applied Pharmaceutical Research, 2018)
Biomedical waste may be defined as the waste which is produced during the diagnosis, research activities, treatment of patients, treatment of animals, production and testing of biological product and including articles as mentioned in schedule I of the Biomedical Waste (Management and handling) (second amendment) Rules 2000, as per Ministry of Environment and Forests notification. Proper treatment, handling, and disposal of biomedical wastes is essential for healthcare infection control program. There may be a high risk of infections in patients due to the poor management of biomedical waste which can lead to antibiotic resistance. It is not only the health of the patient, but also the health of persons who are associated with health care industry equally important. This article speaks about how the hospitals present in Guwahati treat their waste material and the effect of the waste in the environment